1993
DOI: 10.1007/bf00864227
|View full text |Cite
|
Sign up to set email alerts
|

The influence of electrode position on bipolar surface electromyogram recordings of the upper trapezius muscle

Abstract: The effect of electrode position on the upper trapezius muscle on the myo-electric signal amplitude was investigated with special reference to arm position and estimate of force output. Previously, a depression of the electromyogram (EMG) signal has been reported midway between the seventh cervical vertebrae (C7) and acromion (Veiersted 1991, Eur J Appl Physiol 62:91-98) although this electrode position has been recommended (Zipp 1982, Eur J Appl Physiol 50: 41-54). Ten healthy subjects performed maximal shoul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
130
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(138 citation statements)
references
References 14 publications
7
130
0
1
Order By: Relevance
“…One possible explanation for the large variation is methodological. We paid particular attention to the electrode placement; they were not placed over the end-plate region (29). Thus the risk for cross-talk from signals originating in adjacent muscles was small.…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for the large variation is methodological. We paid particular attention to the electrode placement; they were not placed over the end-plate region (29). Thus the risk for cross-talk from signals originating in adjacent muscles was small.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental Procedure Surface electrodes were placed over the upper trapezius muscle (two thirds of the distance from the spinous process of the seventh cervical vertebra to the acromial process), 50 the lower trapezius muscle (one fourth of the distance from the thoracic spine to the inferior angle of the scapula when the arm was fully flexed in the sagittal plane), 51 and the lower serratus anterior muscle (over the muscle fibers anterior to the latissimus dorsi muscle when the arm was flexed 90°in the sagittal plane) 52 ( Fig. 1A).…”
Section: Instrumentationmentioning
confidence: 99%
“…Electrode placement (FIGURE 1) was based on the work of Cram and Kasman 10 and Jensen et al 19 The electrodes for the upper trapezius muscle were placed approximately 2 cm lateral to the midpoint of an imaginary line connecting the spinous process of the seventh cervical vertebra and the acromion ( just lateral to where the scapular tape was placed). Electrode placement for the lower trapezius muscle was approximately 10.5 cm inferomedial to the medial border of the spine of the scapula, at a 55° oblique angle to the horizontal plane, but not below T12.…”
Section: Instrumentationmentioning
confidence: 99%
“…In addition, the location of the upper trapezius electrode was midway between the C7 spinous process and the acromion in the Cools et al 7 study, which has been reported to depress the signal amplitude of the upper trapezius. 19 They applied the tape lateral to the electrodes and laterally over the upper trapezius. Perhaps the most important difference between the 2 studies involves the subject populations: the current study used injured individuals rather than noninjured subjects.…”
Section: Comparison To the Literaturementioning
confidence: 99%